Discovering your expressive body [videorecording] basic dance concepts in dance training utilizing Bartenieff fundamentals - Hackney, Peggy (Peggy Hackney and Diane Ramsey, 1981)
This comprehensive demonstration provides a basis for expanded knowledge knowledge of movement principles that lead to an articulate, more expressive body.